1982
DOI: 10.1139/v82-196
|View full text |Cite
|
Sign up to set email alerts
|

Confacial bioctahedral complexes of tungsten(IV) containing tungsten-to-tungsten bonds: X-ray crystal structures of di-μ-ethanethiolato-μ-sulfidobis[dichloro(dimethyl sulfide)-tungsten(IV) (W—W)] and tetraphenylphosphonium di-μ-ethane thiolato-μ-sulfido- bis[trichlorotungstate(IV) (W—W)]

Abstract: . Can. J. Chem. 60, 1333 (1982).The complex (Me,S)Cl,W(p-S)(p-SEt)zWC1z(Me,S), 1, has been prepared by reaction of [WCI,(Me,S),] with 1 mol-equiv. of SiMe,(SEt) in CH,Cl, solution. A single-crystal X-ray diffraction study shows that the molecule has a confacial bioctahedral structure with a W-W bond length of2.526(2) A. The structure was solved by heavy atom methods and refined to R = 0.061 and R,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1983
1983
1993
1993

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…1). Recent studies in our laboratory have shown that the W-SR group in complexes of tungsten(1V) is unstable as a terminal entity (2)(3)(4)(5). By metathesis of WC14L, (L = Me2S; C4H8S) with SiMe3(SR) (R = alkyl, aryl), the intermediates WC4-,(SR),,L2, 2, have been prepared via the equation: \ 2 can undergo degradation by one of two observed pathways, depending on the stoichiometry (i.e.…”
mentioning
confidence: 99%
“…1). Recent studies in our laboratory have shown that the W-SR group in complexes of tungsten(1V) is unstable as a terminal entity (2)(3)(4)(5). By metathesis of WC14L, (L = Me2S; C4H8S) with SiMe3(SR) (R = alkyl, aryl), the intermediates WC4-,(SR),,L2, 2, have been prepared via the equation: \ 2 can undergo degradation by one of two observed pathways, depending on the stoichiometry (i.e.…”
mentioning
confidence: 99%